Conductive laminate, bonded structure using same, spontaneous potential measuring sensor, chloride ion sensor, and method for producing same
The conductive laminated body with a conductive layer and adhesive layer, using specific materials, addresses the issue of conductivity and durability in outdoor environments, enabling long-term sensor use for reinforced concrete monitoring.
Patent Information
- Application Number
- JP2020187290
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-17
- Filing Date
- 2020-11-10
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-11-10
AI Technical Summary
Existing conductive adhesive sheets lack high conductivity, durability, and adhesion in outdoor environments, making them unsuitable for long-term use in monitoring sensors for reinforced concrete deterioration.
A conductive laminated body with a conductive layer and a conductive hot melt adhesive layer having specific resistance and elasticity values, combined with conductive fillers like graphite and thermoplastic resins, ensures high conductivity and durability.
The conductive laminated body provides stable electrical signals for long-term use in natural potential and chloride ion sensors, maintaining conductivity and adhesion in outdoor conditions.
Smart Images

Figure 0007625830000008 
Figure 0007625830000009 
Figure 0007625830000010
Abstract
Description
[Technical field]
[0001] The present invention is applicable to conductive adherends, such as materials such as stone, stainless steel, concrete, skin, and wood. strength The present invention relates to a conductive laminate adhesive sheet that is capable of acquiring electrical signals from within an adherend while firmly adhering, and a method for producing the same. [Background technology]
[0002] In recent years, with the rapid advancement of information technology, the development of devices that can obtain information more accurately, for a long time, and with less power consumption is being actively carried out both in Japan and overseas. In particular, the progress of sensor technology has been tremendous, and by installing sensors in all sorts of places, it is possible to obtain information that was previously difficult to handle or that had to rely on on-site skilled techniques with high accuracy and semi-permanently, and the improvement of sensor attachment and fixing technology has made it possible to obtain information easily. In this context, there is a growing demand for conductive adhesive sheets that can easily and firmly bond and adhere conductive materials to objects, and can obtain electrical signals from the objects for long periods of time. As technological advances in the electronics field progress, modularization of electronic materials is progressing, and conductive adhesive sheets are indispensable in such fields. In addition, by firmly adhering such a conductive adhesive sheet to the surface of reinforced concrete, it can be used as a monitoring sensor for diagnosing deterioration of reinforced concrete. However, a conductive adhesive sheet that can be easily attached and has high conductivity, adhesive strength, and durability in outdoor environments has not yet been realized. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-200225 A [Patent Document 2] JP 2002-155261 A Summary of the Invention [Problem to be solved by the invention]
[0004] The object of the present invention is to provide a method for producing a highly conductive material for an adherend. strength The present invention aims to provide a conductive laminate that can be firmly bonded. [Means for solving the problem]
[0005] As a result of intensive research by the present inventors to solve the above problems, it has been found that the following conductive laminate can be used strength This led to the discovery that a strong conductive adhesion could be achieved, and thus the present invention was completed.
[0006] That is, the present invention provides a conductive laminate having at least a conductive layer and a conductive hot melt adhesive layer in contact with the conductive layer on a substrate, the conductive hot melt adhesive layer having a volume resistivity of 1×10 -1 Ωcm or more 1×10 3 The volume resistivity of the conductive layer is less than 1×10 -5 Ωcm or more 1×10 0 The present invention relates to a conductive laminate having a resistivity of less than Ωcm.
[0007] The present invention also relates to the aforementioned conductive laminate, wherein the conductive hot-melt adhesive layer has an elastic modulus of less than 5 MPa at 25°C.
[0008] The present invention also relates to the aforementioned conductive laminate, wherein the conductive layer and / or the conductive hot-melt adhesive layer is patterned.
[0009] The present invention also relates to the above-mentioned conductive laminate, characterized in that it has a patterned insulating hot-melt adhesive layer around the periphery of the patterned conductive layer and / or the patterned conductive hot-melt adhesive layer.
[0010] The present invention also relates to the aforementioned conductive laminate, wherein the conductive layer and the conductive hot-melt adhesive layer each contain a resin and a conductive filler.
[0011] The present invention also relates to the conductive laminate, wherein the conductive filler is at least one selected from the group consisting of graphite, carbon black, carbon nanotubes, graphene, graphene oxide, silver, copper, tin, zinc, zinc oxide, nickel, manganese, and ITO.
[0012] The present invention also relates to the aforementioned conductive laminate, wherein the conductive filler contains at least one selected from the group consisting of graphite, carbon black, carbon nanotubes, graphene, and graphene oxide.
[0013] The present invention also relates to the aforementioned conductive laminate, wherein the resin in the conductive hot melt adhesive layer contains a styrene-based thermoplastic resin, and the resin in the conductive layer contains a phenoxy-based thermoplastic resin.
[0014] The present invention also relates to the aforementioned conductive laminate, wherein the conductive hot-melt adhesive layer and / or the insulating hot-melt adhesive layer has adhesiveness.
[0015] The present invention also relates to a bonded structure comprising the above-mentioned conductive laminate and an adherend laminated thereon.
[0016] The present invention also provides a self-potential sensor capable of measuring deterioration of reinforcing bars present inside concrete through a signal obtained from a conductive laminate, comprising: The present invention relates to a spontaneous potential measuring sensor, characterized in that the conductive laminate is the conductive laminate described above.
[0017] The present invention also provides a chloride ion sensor capable of measuring a chloride ion concentration inside concrete through a signal obtained from a conductive laminate, comprising: The present invention relates to a chloride ion sensor, characterized in that the conductive laminate is the conductive laminate described above.
[0018] The present invention also relates to a method for producing a conductive laminate having at least a conductive layer and a conductive hot melt adhesive layer adjacent to the conductive layer on a substrate, the method comprising the steps of: printing the conductive layer on the substrate; and printing the conductive hot melt adhesive layer, the volume resistivity of the conductive hot melt adhesive layer being 1×10 -1 Ωcm or more 1×10 3 The volume resistivity of the conductive layer is less than 1×10 -5 Ωcm or more 1×10 0 The present invention relates to a method for producing a conductive laminate, characterized in that the resistivity is less than Ωcm. Effect of the Invention
[0019] According to the present invention, it is possible to provide a conductive laminate that exhibits high electrical conductivity, adhesive strength, and durability. Furthermore, the conductive laminate described above can provide a sensor that can be used for a long period of time. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 shows an example of the configuration of the conductive laminate of the present invention and an adhesive structure in which the conductive laminate and an adherend are laminated together. [Diagram 2] FIG. 2 shows an example of the configuration of the conductive laminate of the present invention and an adhesive structure in which the conductive laminate and an adherend are laminated together. [Diagram 3] FIG. 3 shows examples of the configuration of the conductive laminate of the present invention and an adhesive structure in which the conductive laminate and an adherend are laminated together. [Figure 4] FIG. 4 shows examples of the configuration of the conductive laminate of the present invention and an adhesive structure in which the conductive laminate and an adherend are laminated together. [Diagram 5] FIG. 5 shows a representative embodiment showing an example of installation of the self-potential sensor of the present invention. [Figure 6] FIG. 6 shows a representative embodiment illustrating an example of installation of the chloride ion sensor of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, an embodiment of the present invention will be described.
[0022] <Conductive laminate> The conductive laminate of the present invention is a conductive laminate having at least a conductive layer and a conductive hot melt adhesive layer in contact with the conductive layer on a substrate, the conductive hot melt adhesive layer having a volume resistivity of 1×10 -1 Ωcm or more 1×10 3 The volume resistivity of the conductive layer is less than 1×10 -5 Ωcm or more 1×10 0 It is characterized by a resistivity of less than Ωcm.
[0023] The conductive laminate consisting of the conductive hot melt adhesive layer and the conductive layer has a structure in which these layers are laminated, and thus it is possible to achieve both conductivity and adhesion. When a metal foil is used instead of the conductive laminate, the durability is low, and there is a risk that the conductive properties will deteriorate over time, but by using the conductive laminate of the present invention, it is possible to use it in a state where the conductivity is maintained for a long period of time even under external environments. In particular, it is preferable that the conductive hot melt adhesive layer and the conductive layer contain a thermoplastic resin and a conductive filler.
[0024] <Conductive filler> Examples of the conductive filler used in the present invention include metals such as silver, gold, copper, nickel, zinc, manganese, iron, cobalt, and aluminum, and alloys thereof; metal oxides such as zinc oxide, tin oxide-doped indium oxide (ITO), tin oxide-doped indium oxide (FTO), tin oxide (IO), neodymium-barium-indium oxide, and indium zinc oxide (IZO); organic substances such as polythiophenes, polypyrroles, polyanilines, and oligothiophenes; inorganic insulators such as alumina and glass; and polymers such as polyethylene and polystyrene, whose surfaces are coated with a conductive substance; and carbon-based substances such as carbon black, graphite, graphene, graphite, carbon nanotubes, fullerenes, graphene oxide, and acetylene black, but are not limited to these. Also, preferred are graphite, carbon black, carbon nanotubes, graphene, graphene oxide, silver, copper, tin, zinc, zinc oxide, nickel, manganese, and ITO, and more preferred are graphite, carbon black, carbon nanotubes, graphene, and graphene oxide. These may be used alone or in combination of two or more. These fillers may have a structure in which two or more types of layers are connected together by coating or the like. The conductive filler is preferably carbon-based because it has excellent resistance to various types such as heat resistance, water resistance, and acid resistance. Also, since the conductive filler is dispersed in the thermoplastic resin, it is retained within the conductive laminate without dissociating and penetrating into the adherend.
[0025] The shape of the conductive filler may be, but is not limited to, flake (scale), spherical, needle-like, fibrous, or dendritic. If it is desired to reduce the amount of conductive filler added in order to strengthen the adhesive strength, flake (scale) filler and a mixture of flake (scale) filler and other conductive filler are preferred.
[0026] The content ratio of the conductive filler in the entire conductive hot melt adhesive layer is not particularly limited, but from the viewpoint of adhesive strength and electrical conductivity, the content is preferably 2 to 65% by weight for carbon-based materials such as carbon black and graphite, and more preferably 5 to 40% by weight. If it is less than 2% by weight, the electrical conductivity may be insufficient, and if it exceeds 65% by weight, the adhesive strength may be insufficient.
[0027] The content ratio of the conductive filler to the entire conductive layer is not particularly limited, but for carbon-based fillers such as carbon black and graphite, it is preferably 10 to 80% by weight, more preferably 20 to 75% by weight, and even more preferably 30 to 70% by weight, from the viewpoint of conductivity and adhesive strength. If it is less than 10% by weight, the conductivity may be insufficient, and if it exceeds 80% by weight, the adhesive strength may be insufficient. On the other hand, for metal fillers such as silver and copper, it is preferably 40 to 80% by weight, more preferably 50 to 70% by weight. If it is less than 40% by weight, the conductivity may be insufficient, and if it exceeds 80% by weight, the adhesive strength may be insufficient.
[0028] <Thermoplastic resin> The thermoplastic resin may be a so-called hot melt resin, which is a non-curable resin that becomes flowable at high temperatures and returns to a non-flowable state upon cooling, or a curable resin, which undergoes a curing (crosslinking) reaction after the thermoplastic resin is applied to a substrate.
[0029] The thermoplastic resin may include one or more selected from the group consisting of thermoplastic resins including polyurethane, acrylonitrile, diene, acrylic, butadiene, polyamide, polyvinyl butyral, olefin, isoprene, butadiene, chloroprene, acrylonitrile, polyester, polyvinyl chloride, styrene, phenoxy, ethylene-vinyl acetate, fluorine, silicone, and copolymers thereof. However, the thermoplastic resin is not limited to these resins. From the viewpoints of reducing damage caused by lamination, durability, weather resistance, heat resistance, and adhesive strength, it is more preferable that the hot melt adhesive layer contains a styrene thermoplastic resin and the conductive layer contains a phenoxy thermoplastic resin. The thermoplastic resin may be used alone or in combination of two or more types. Furthermore, the thermoplastic resin may be a copolymer formed by linking different monomers.
[0030] Styrene-based thermoplastic resins, specifically styrene-based elastomers, are preferably used for conductive hot melt adhesive layers, and generally have a polystyrene block and a rubber middle block, with the polystyrene portion forming a physical crosslink (domain) and becoming the crosslinking point, and the middle rubber block giving the product rubber elasticity. The middle soft segment includes polybutadiene (B), polyisoprene (I) and polyolefin elastomer (ethylene propylene, EP), and depending on the arrangement with the hard segment polystyrene (S), they are divided into linear type and radial type. Among the above-mentioned preferred styrene-based elastomers, the present invention may more specifically include at least one selected from the group consisting of styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-ethylene-butylene-styrene block copolymer (SEPS), styrene-butylene-styrene block copolymer (SBS), hydrogenated styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-isoprene-styrene block copolymer (SBIS) and hydrogenated styrene-butadiene-isoprene-styrene block copolymer (SEEPS), but is not limited to these resins.
[0031] Phenoxy-based thermoplastic resins are preferably used for the conductive layer, and can generally be obtained by the reaction of a phenolic compound with epichlorohydrin, but known phenoxy-based thermoplastic resins can be used. The phenoxy-based thermoplastic resins used here are not particularly limited, and examples thereof include phenoxy-based thermoplastic resins having a bisphenol skeleton such as bisphenol A type, bisphenol F type, bisphenol A-F mixed type, and bisphenol S type, as well as phenoxy-based thermoplastic resins having a naphthalene skeleton and phenoxy-based thermoplastic resins having a biphenyl skeleton. From the viewpoint of handling, the weight-average molecular weight of the phenoxy-based thermoplastic resin is preferably 10,000 to 100,000. It is more preferably 20,000 to 80,000.
[0032] <Tackifier> Examples of tackifiers include hydrogenated terpene resins, terpene resins, hydrogenated rosin resins, rosin resins, hydrogenated hydrocarbon resins, hydrocarbon resins, epoxy resins, hydrogenated epoxy resins, ketone resins, hydrogenated ketone resins, polyamide resins, hydrogenated polyamide resins, elastomer resins, hydrogenated elastomer resins, phenol resins, hydrogenated phenol resins, petroleum resins, hydrogenated petroleum resins, styrene resins, and hydrogenated styrene resins. These tackifier resins can be used alone or in combination. Among these, hydrogenated hydrocarbon resins are preferred from the viewpoint of durability. Hydrogenation eliminates the conjugated double bonds in the molecular structure, so conductive hot melt adhesives containing tackifiers are less likely to deteriorate due to light or heat when permanently bonded to an adherend, making it possible to maintain adhesive strength for 10 years or more.
[0033] <Softener> Examples of the softener include petrolatum, mineral oil, vegetable oil, and animal oil. Examples of the mineral oil include liquid paraffin, paraffin, paraffin-based mineral oil in which the number of carbon atoms in the paraffin chain accounts for 50% or more of the total number of carbon atoms, naphthenic mineral oil in which the number of carbon atoms in the naphthenic ring accounts for 30 to 40% by weight of the total number of carbon atoms, and aromatic mineral oil in which the number of aromatic carbon atoms accounts for 30% by weight or more of the total number of carbon atoms. Vegetable oils and fats: Olive oil, carnauba wax, rice germ oil, corn oil, camellia oil, castor oil, jojoba seed oil, mink oil, eucalyptus leaf oil, and the like. Animal oils and fats: Beeswax, squalane, and honey. Other examples of softening agents include myristic acid, oleic acid, isopropyl myristic acid, zinc myristic acid, octyldodecyl myristate, glycerin triisooctanoate, octyldodecanol, hexyldecanol, diisopropyl adipate, diethyl sebacate, stearic acid, isostearic acid, crotamiton, medium-chain triglyceride, ethylene glycol salicylate, cetyl ethylhexanoate, glycol distearate, cetearyl alcohol, cetanol, cetyl palmitate, ethylhexyl palmitate, isopropyl palmitate, and behenyl alcohol. The softener may contain a plasticizer, and examples thereof include dioctyl phthalate, diisodecyl phthalate, bis-2-ethylhexyl phthalate, dibutyl phthalate, dicyclohexyl phthalate, diisononyl phthalate, tributyl acetylcitrate, dioctyl adipate, diisononyl adipate, tricresyl phosphate, trioctyl trimellitate, etc. These softeners may be used alone or in combination of two or more.
[0034] <Antioxidants> Examples of the antioxidant include pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, diethyl [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-t-butyl)-4-hydroxyphenyl]methyl]phosphonate, and the like. Examples of the phenol-based antioxidant include pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, etc. The phenol-based antioxidant is preferably pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], and the phosphorus-based antioxidant is preferably tris(2,4-di-t-butylphenyl)phosphite.
[0035] <Dispersant> The addition of a dispersant is effective for controlling the fluidity and viscosity when forming the conductive hot melt adhesive layer and the conductive layer by a printing / coating method, and is particularly effective when a solvent is used. The content of the dispersant can be appropriately selected depending on the purpose of use, but it is preferably 10 to 300% relative to the conductive filler. The dispersant used can be obtained commercially, for example, DISPERBYK-102, DISPERBYK-103, DISPERBYK-106, DISPERBYK-108, DISPERBYK-110, DISPERBYK-111, DISPERBYK-130, DISPERBYK-140, DISPERBYK-150, DISPERBYK-160, DISPERBYK-161, DISPERBYK-162, DISPERBYK-163, DISPERBYK-164, DISPERBYK-165, DISPERBYK-180, DISPERBYK-190, DISPERBYK-1 91, DISPERBYK-198, DISPERBYK-2000, DISPERBYK-2001, DISPERBYK-2010, DISPERBYK-2012, DISPERBYK-2015, DISPERBYK-2022, DISPERBYK-2055, DISPERBYK-2096, DISPERBYK-2155, DISPERBYK-2164, BYK-9076, BYK-9077, BYKOPLAST-1000, DISPERPLAST-1018, DISPERPLAST-1018, DISPERPLAST-1042, DISPERPLAST-1150, and the like, but are not limited to these.
[0036] <Other ingredients> The conductive hot melt adhesive layer and the conductive layer can be appropriately mixed with various additives as long as the effects of the present invention are not impaired. For example, from the viewpoints of reducing the cure shrinkage rate, reducing the thermal expansion rate, improving dimensional stability, improving the elastic modulus, adjusting the viscosity, improving strength and improving toughness, curing agents such as polyisocyanates, epoxy resins, polycarbodiimide compounds, and amine-based compounds, and organic or inorganic fillers can be mixed. Such fillers may be composed of materials such as polymers, ceramics, metal salts, and dyes and pigments. In addition, the shape is not particularly limited, and may be, for example, particulate or fibrous. In addition, in order to adjust the leveling property with the substrate, the coating property during coating printing, and improve adhesion, silane coupling agents, titanate coupling agents, flame retardants, storage stabilizers, antioxidants, metal deactivators, ultraviolet absorbers, thixotropy-imparting agents, leveling agents, dispersion stabilizers, fluidity-imparting agents, defoamers, and coloring materials can also be added.
[0037] <Conductive hot melt adhesive layer> The method for producing the conductive hot melt adhesive layer of the present invention is not particularly limited, but an example is shown below. In addition to the conductive filler, a thermoplastic resin and, if necessary, a softener, a tackifier, an antioxidant, and other optional components are mixed to form a mixture. The mixture is dispersed by a known dispersing machine to form a dispersion, but the order of mixing is not particularly limited, and a dispersion in which a thermoplastic resin, a softener, and a tackifier are dispersed in advance and a mixture of a conductive filler may be dispersed. Examples of dispersing machines include roll mills such as two-roll and three-roll, ball mills such as ball mills and vibration ball mills, paint conditioners, bead mills such as continuous disk bead mills and continuous annular bead mills, and Banbury mixers, kneaders, melting pots equipped with stirrers, and single- or twin-screw extruders. Next, after a heat-melting process in which these are heated and mixed, or a dissolving process in which they are dissolved in an appropriate solvent and stirred and mixed, the resulting mixture can be obtained through a printing and coating process described below. The conductive hot melt adhesive layer used in the present invention can be obtained by a heat melting process that does not use a solvent, from the viewpoint of the complication of the process due to the solvent removal and the associated increase in cost, and further from the viewpoint of the adverse effect on the global environment due to the use of a solvent. In addition, when the conductive hot melt adhesive layer used in the present invention contains a carbon-based filler, the fluidity is extremely reduced, so in consideration of the coatability, printability, and uniform dispersion, it is preferable to include a process using a solvent. The conductive hot melt adhesive layer used in the present invention can be used with only a conductive filler and a thermoplastic resin, but it is preferable to include a softener, a tackifier, an antioxidant, and a dispersant from the viewpoint of fluidity, adhesion, and oxidation stability. The thickness of the conductive hot melt adhesive layer used in the present invention is not particularly limited, but is preferably 10 to 500 μm, more preferably 50 to 400 μm, and even more preferably 100 to 300 μm. The conductive hot melt adhesive layer used in the present invention is disposed on the surface of the adherend and used. The conductive hot melt adhesive layer used in the present invention may be directly attached to the adherend, but after being attached to the surface of the adherend, it can be melted by heating and solidified by cooling, so that it can be held in close contact with the surface of the adherend and stably maintained.In addition, the conductive hot melt adhesive layer fills voids on the surface of the adherend, thereby suppressing contact resistance. For ease of bonding to an adherend, the conductive hot-melt adhesive layer preferably has adhesive properties.
[0038] <Conductive layer> The method for producing the conductive layer of the present invention is not particularly limited, but an example will be described below. The conductive layer is a mixture of the conductive filler and resin, and if necessary, softeners, tackifiers, antioxidants, dispersants, and other optional components. The resin may be a thermoplastic resin, a heat-curable resin, or a photo-curable resin, but it is preferable to use a thermoplastic resin from the viewpoint of flexibility. The conductive layer can ensure high conductivity by using a metal filler such as aluminum or copper, but it is preferable to use a conductive layer in which a resin and a conductive filler are mixed from the viewpoint of durability. The thickness of the conductive layer used in the present invention is not particularly limited, but is preferably 5 to 100 μm, and more preferably 10 to 50 μm. The mixture is dispersed by a known dispersing machine to obtain a dispersion. Examples of the dispersing machine include roll mills such as two-roll and three-roll, ball mills such as ball mills and vibration ball mills, paint conditioners, continuous disk-type bead mills and continuous annular-type bead mills, and bead mills such as Banbury mixers, kneaders, melting pots equipped with stirrers, and single- or twin-screw extruders. Next, these are dissolved in a suitable solvent and stirred and mixed in a solvent-based process, after which the product can be obtained through a printing and coating process described below.
[0039] <Insulating hot melt adhesive layer> The method for producing the insulating hot melt adhesive layer of the present invention is not particularly limited, but an example is shown below. A thermoplastic resin, a softener, a tackifier, an antioxidant, and other optional components used as necessary are mixed to form a mixture. The mixture is mixed by a known dispersing machine or agitator to form a mixture, but the order of mixing is not particularly limited. Examples of dispersing machines or agitators include roll mills such as two-roll and three-roll, ball mills such as ball mills and vibration ball mills, paint conditioners, continuous disk-type bead mills, continuous annular-type bead mills, and the like, and also include Banbury mixers, kneaders, melting pots equipped with agitators, and single- or twin-screw extruders. Next, after a heat-melting process in which these are heated and mixed, or a solvent-type process in which the materials are dissolved in an appropriate solvent and stirred and mixed, the resulting insulating hot melt adhesive layer can be obtained through a printing and coating process described below. The insulating hot melt adhesive layer used in the present invention can be obtained using a heat-melting process that does not use a solvent, from the viewpoint of the complication of the process due to the removal of the solvent and the associated increase in costs, and from the viewpoint of the adverse effect on the global environment due to the use of the solvent. In addition, the insulating hot melt adhesive layer used in the present invention preferably includes a process using a solvent, taking into consideration film thickness controllability, coatability, and printability. The insulating hot melt adhesive layer used in the present invention can be used with only a thermoplastic resin, but it is preferable to include a softener, a tackifier, and an antioxidant from the viewpoint of fluidity, adhesion, and oxidation stability. The thickness of the insulating hot melt adhesive layer used in the present invention is not particularly limited, but is preferably 10 to 500 μm, more preferably 50 to 400 μm, and even more preferably 100 to 300 μm. The insulating hot melt adhesive layer used in the present invention is effective when the conductive hot melt adhesive layer does not have adhesion or adhesiveness, and by imparting adhesion or adhesiveness to the hot melt adhesive layer instead of the conductive hot melt adhesive layer, the conductive laminate can be easily placed on the surface of the adherend. The insulating hot melt adhesive layer used in the present invention is placed on the surface of the adherend. The insulating hot melt adhesive layer used in the present invention may be directly attached to the adherend by utilizing its adhesiveness, but after being attached to the surface of the adherend, it can be melted by heating and solidified by cooling, so that it can be held in close contact with the surface of the adherend and stably maintained. The volume resistivity of the insulating hot melt adhesive layer is set to 1×10 5 It is preferable that the volume resistivity of the insulating hot melt adhesive layer is 1×10 10 More preferably, it should be 1×10 15 Ω cm or more 1×10 20 A value of less than Ω·cm is even more preferable.
[0040] <Conductive laminate> The conductive laminate of the present invention can be used as a conductive laminate by forming a conductive layer on one side of a substrate as shown in Fig. 1 and forming a conductive hot melt adhesive layer on the conductive layer. Furthermore, the conductive laminate may have a sealing layer as shown in Fig. 2. Furthermore, the conductive laminate can be used as a conductive laminate by forming an insulating hot melt adhesive layer around the conductive layer and the conductive hot melt adhesive layer formed on the same substrate as shown in Fig. 3. Furthermore, the conductive laminate may be one in which wiring provided on the spontaneous potential sensor or chloride ion sensor is connected to the conductive laminate as shown in Fig. 4. The conductive layer may be formed by coating or printing, but is not particularly limited thereto. Coating methods include slot spray coating, omega coating, spiral coating, control seam coating, slot spray coating, dot coating, hot melt applicator coating, hot melt coater coating, blade coat coating, dip coating, gravure coat coating, curtain spray coating, bead coating, and hot melt roll coater spin coat coating. Printing methods include inkjet printing, spray printing, roll coat printing, doctor roll printing, doctor blade printing, curtain coat printing, slit coat printing, screen printing, reverse printing, push coat printing, slit coater printing, and stencil printing. Drying conditions when a solvent is used are not particularly limited, and include hot air drying, infrared rays, and reduced pressure methods. Drying conditions vary depending on the film thickness and the organic solvent selected, but hot air heating at about 60 to 200°C is usually used. The thickness of the conductive layer is not particularly limited, but is preferably 5 to 50 μm. The conductive layer can also be crosslinked by heating or irradiating with ultraviolet light. Examples of the method for forming the conductive hot melt adhesive layer include coating and printing methods, and are not particularly limited. Examples of the coating method include slot spray coating, omega coating, spiral coating, control seam coating, slot spray coating, dot coating, hot melt applicator coating, hot melt coater coating, blade coat coating, dip coating, gravure coat coating, curtain spray coating, bead coating, and hot melt roll coater spin coat coating. Examples of the printing method include inkjet printing, spray printing, roll coat printing, doctor roll printing, doctor blade printing, curtain coat printing, slit coat printing, screen printing, reverse printing, transfer printing, push coat printing, slit coater printing, and stencil printing. The drying conditions when a solvent is used are not particularly limited, and include hot air drying, infrared rays, and reduced pressure methods. Drying conditions vary depending on the film thickness and the selected organic solvent, but typically involve hot air heating at about 60 to 200°C. The thickness of the conductive hot melt adhesive layer is preferably 50 to 400 μm. The conductive hot melt adhesive layer can also be crosslinked by heating or ultraviolet irradiation. When a substrate is not required, a conductive laminate similar to that described above may be formed using a peelable substrate, and then the substrate may be peeled off.
[0041] Examples of the method for forming the conductive hot melt adhesive layer or the insulating hot melt adhesive layer include coating and printing methods, and are not particularly limited. Examples of the coating method include slot spray coating, omega coating, spiral coating, control seam coating, slot spray coating, dot coating, hot melt applicator coating, hot melt coater coating, blade coat coating, dip coating, gravure coat coating, curtain spray coating, bead coating, and hot melt roll coater spin coat coating, and examples of the printing method include inkjet printing, spray printing, roll coat printing, doctor roll printing, doctor blade printing, curtain coat printing, slit coat printing, screen printing, reverse printing, transfer printing, push coat printing, and slit coater printing. The drying conditions when a solvent is used are not particularly limited, and examples include hot air drying, infrared rays, and reduced pressure methods. Drying conditions vary depending on the film thickness and the selected organic solvent, but typically involve hot air heating at about 60 to 200°C. The thickness of the conductive hot melt adhesive layer or the insulating hot melt adhesive layer is preferably 50 to 400 μm. The conductive hot melt adhesive layer or the insulating hot melt adhesive layer can also be crosslinked by heating or ultraviolet irradiation. When a substrate is not required, a conductive laminate similar to that described above may be formed using a peelable substrate, and then the substrate may be peeled off. When the conductive layer, the conductive hot-melt adhesive layer or the insulating hot-melt adhesive layer is patterned, the various printing methods described above can be used.
[0042] <Base material> The substrate is selected from the group consisting of a resin sheet, paper, and an aluminum sheet (aluminum foil). For example, the resin sheet may be a resin sheet formed from a resin such as a polyester resin such as polyethylene terephthalate (PET) or polyethylene naphthalate (PEN), a polycarbonate resin, a polyarylate resin, an acrylic resin, a polyphenylene sulfide resin, a polystyrene resin, a vinyl resin, a vinyl chloride resin, a polyimide resin, an epoxy resin, or a polyolefin resin such as polyethylene, polypropylene, or polynorbornene. In addition, the substrate may be a laminate in which a metal is laminated on these sheets, for example, a laminate in which a metal is laminated on a polyethylene terephthalate (PET) sheet. In addition, since the substrate may be deformed by heat, a substrate with high heat resistance such as a polyimide sheet, a polyethylene naphthalene sheet, a polynaphthalene sheet, a propylene sheet, or a silicone resin sheet, or a substrate with improved heat resistance due to filling with a filler, is preferable.
[0043] <Adhesive structure> An adhesive structure can be produced by attaching or placing the surface of the conductive hot melt adhesive layer of the conductive laminate on an adherend, and melting the conductive hot melt adhesive layer on the adherend using, but not limited to, an iron, heater, electric heating wire, hot air, infrared heater, IH heating device, etc., to bond the conductive hot melt adhesive layer to the adherend.
[0044] <Adherend> Examples of the adherend include plastic, paper, a composite of paper and plastic, silver, stainless steel, copper, iron, aluminum, alloys, minerals, non-ferrous metals, concrete, mortar, slate, tiles, paving materials, skin, wood, cloth, leather, rubber, cork, glass, etc. The thickness of the adherend of the present invention is preferably 1 mm or more. The type of adherend used in the present invention is not particularly limited, but concrete and mortar are preferred because they contain a large amount of electrolytes such as chloride ions, sodium ions, and calcium ions, as well as water, as described below, making it easy to receive signals from the inside. The concrete and mortar mentioned here are a mass of cement mixed with water and hardened over time. It may contain fine aggregates such as sand and coarse aggregates such as gravel. Concrete hardens by the dissolution and precipitation reaction of cement. Cement is composed of elements such as calcium, silicon, aluminum, and iron. When it comes into contact with water, calcium ions dissolve and the calcium ions in the aqueous solution increase. The main components, silicic acid (SiO2) and alumina (Al2O3), exist as stable substances (polymers) in which the ions are polymerized with each other and do not react with calcium ions. However, in cement, silicate ions and aluminum ions (alumina ions) exist as monomers that react relatively easily, and when the surrounding calcium ions are leached out, they dissolve into the solution and react with calcium ions and water molecules to form cement hydrate (CSH: ettringite), which is difficult to dissolve in water, and the remaining calcium ions precipitate as calcium hydroxide. The hydrate particles bond to each other and harden. The bonds between particles are thought to be held together by intermolecular attraction and hydrogen bonds, and unlike calcium hydroxide, CSH has fine bonds of 0.1 μm or less, and the bonding area between particles per unit volume is significantly large, so it exerts high bonding strength and strength in the hardened body. The concrete layer of the present invention can be made of cement made by mixing and hardening cement and water, mortar made by mixing and hardening cement, water, and fine aggregate (sand), and concrete made by mixing and hardening cement, water, and aggregate (fine aggregate (sand) and coarse aggregate (gravel)).
[0045] <Self-potential sensor> In order to judge corrosion of steel materials such as reinforcing bars arranged in concrete structures, long-term monitoring by constructing a sensor system is necessary. A natural potential measurement method is known as a method for judging corrosion of steel materials such as reinforcing bars in concrete structures. The natural potential measurement method is a method for electrochemically judging corrosion of steel materials by measuring the potential of the steel material that changes due to corrosion. As shown in FIG. 5, the conductive laminate of the present invention is attached to concrete, and the progress of reinforcing bar corrosion can be detected by measuring the potential difference between the concrete and the reinforcing bar, and this can be used as a natural potential sensor. In addition, by using the conductive laminate of the present invention, a natural potential sensor system that can realize a stable contact with high electrical conductivity over a long period of time can be constructed. The natural potential sensor of this embodiment includes a preparation step of preparing a natural potential sensor comprising the conductive laminate of the present invention, an electric wire connection step of electrically connecting wiring provided in the natural potential sensor to the steel material, an adhesion step of adhering the conductive laminate provided in the natural potential sensor to the surface of the concrete structure, and a potential difference detection step of detecting the potential difference between the conductive laminate and the steel material, and the adhesion step includes a step of heating and melting the conductive hot melt adhesive layer or insulating hot melt adhesive layer of the conductive laminate.
[0046] <Chloride ion sensor> In order to estimate the condition of metals such as rebars placed in concrete structures, it is necessary to monitor the chloride ion concentration for a long period of time using a chloride ion sensor. One method for measuring the chloride ion concentration in concrete structures is the conductive method. In general, the conductive method is a method in which an alternating current is passed through a target concrete structure, and the impedance of the concrete structure and the phase angle peak frequency of the impedance are measured, and the chloride ion concentration is calculated by combining this with information such as the moisture content of the concrete structure. As shown in Figure 6, the conductive laminate of the present invention is placed on the surface of a concrete structure at a distance from each other, and by measuring the impedance in a state in which an AC current is passed between at least one pair of conductive laminates, the chloride ion concentration in the concrete structure can be calculated, and this can be used as a chloride ion sensor. The chloride ion sensor of this embodiment includes a preparation step of preparing a chloride ion sensor including the conductive laminate according to the present invention, an electric wire connection step of electrically connecting wiring included in the chloride ion sensor to the conductive laminate, an adhesion step of adhering the conductive laminate included in the chloride ion sensor to the surface of the concrete structure, an adhesion step of adhering at least a pair of conductive laminates included in the chloride ion sensor to the surface of the concrete structure, respectively, and a measurement step of measuring impedance in a state in which an AC current is caused to flow between the at least a pair of conductive laminates via the concrete structure, and the adhesion step includes a step of adhering the conductive hot melt adhesive layer or the insulating hot melt adhesive layer to the concrete structure by heating and melting it.
[0047] <Resistivity> The volume resistivity of the conductive hot melt adhesive layer is set to 1×10 -1 Ω cm or more 1×10 3 It is preferable that the volume resistivity of the conductive hot melt adhesive layer is less than 1×10 Ω·cm. The reason for this is that if the volume resistivity of the conductive hot melt adhesive layer is within this range, a suitable signal can be received from the adherend. Also, it is preferable that the volume resistivity of the conductive hot melt adhesive layer is less than 1×10 0 Ω cm or more 1×10 3 A value of less than 1×10 Ω cm is preferable. 1 A value of less than Ω·cm is even more preferable. The volume resistivity of the conductive layer is set to 1×10 -5 Ωcm or more 1×10 0It is preferable that the volume resistivity of the conductive layer is less than 1×10 Ωcm. The reason for this is that if the volume resistivity of the conductive layer is within this range, the signal received from the conductive hot melt adhesive layer can be received without attenuation. Therefore, it is preferable to set the volume resistivity of the conductive layer to less than 1×10 0 It is preferable to have a value of less than 1×10 Ω cm. -1 It is more preferable that the volume resistivity is less than Ω·cm. The detailed method for measuring the volume resistivity will be specifically described in the Examples.
[0048] <Adhesive strength> The adhesive strength value of the conductive laminate varies depending on the adherend, but the preferred range is 2 N / 25 mm or more and less than 40 N / 25 mm, and more preferably 10 N / 25 mm or more and less than 30 N / 25 mm. The detailed method for measuring the adhesive strength will be specifically described in the Examples.
[0049] <Elasticity modulus> The elastic modulus of the conductive hot melt adhesive layer varies depending on the type of resin or the amount of filler, but since the elastic modulus affects the conformability to the adherend and flexibility, it is preferably less than 5.0 MPa, and more preferably less than 1.0 MPa.
[0050] <Durability> Since it is important for the durability of the conductive laminate to maintain electrochemical stability even in an outdoor environment, the durability was evaluated under salt spray conditions. The detailed measurement method will be specifically described in the Examples. EXAMPLES
[0051] The present invention will be described in detail below with reference to examples, but these examples are merely one embodiment of the present invention and the present invention is not limited to these examples. In the tables, "parts" and "%" refer to "parts by weight" and "% by weight", respectively.
[0052] [Conductive filler adjustment] The filler powders were mixed in the amounts shown in Table 1 to obtain conductive fillers 1 to 21.
[0053] [Preparation of conductive hot melt adhesive layer] 28 parts of SIS1 as a thermoplastic resin, 7 parts of Softener 1 as a softener, 35 parts of Tackifier 4 as a tackifier, 1 part of Antioxidant 1, and 30 parts of Conductive Filler 1 were added to a three-roll mill and kneaded for 30 minutes. The resulting kneaded mixture was stencil printed on a substrate to obtain a conductive hot-melt adhesive layer 1. Conductive hot-melt adhesive layers 2 to 69 were prepared in the same manner as in the preparation of the conductive hot-melt adhesive layer 1, except that the raw materials and composition ratios were changed as shown in Table 2. Note that a polyimide film was used as the substrate.
[0054] [Preparation of conductive layer] Using a three-roll mill, 45 parts of Phenoxy 1 as a thermoplastic resin, 55 parts of Conductive Filler 1 as a conductive filler, and optionally a solvent, dispersant, and defoamer were added and kneaded for 30 minutes, and the resulting kneaded material was screen printed on a substrate to obtain a conductive layer 1. Conductive layers 2 to 8 were prepared in the same manner as for preparing conductive layer 1, except that the raw materials and composition ratios were changed as shown in Table 3. Note that a polyimide film was used as the substrate.
[0055] [Preparation of insulating hot melt adhesive layer] 28 parts of SIS1 as a thermoplastic resin, 7 parts of Softener 1 as a softener, 35 parts of Tackifier 4 as a tackifier, and 1 part of Antioxidant 1 were added to a three-roll mill and kneaded for 30 minutes. The resulting kneaded mixture was stencil printed on a substrate to obtain an insulating hot-melt adhesive layer 1. Except for changing the raw materials and composition ratios as shown in Table 4, insulating hot-melt adhesive layers 2 and 3 were prepared in the same manner as in the preparation of insulating hot-melt adhesive layer 1. Note that a polyimide film was used as the substrate.
[0056] [Preparation of conductive laminate sheet] <Example 1> The conductive hot-melt adhesive layer 1 and conductive layer 1 obtained by the above-mentioned preparation of the conductive hot-melt adhesive layer and preparation of the conductive layer were laminated by printing to form a substrate, a conductive layer 1, and a conductive hot-melt adhesive layer 1 in that order, thereby obtaining Example 1 (conductive laminate sheet 1). Examples 2 to 73 and Comparative Examples 1 to 6 were prepared in the same manner as in Example 1, except that the configuration within the conductive laminate (combination of the conductive hot-melt adhesive layer and the conductive layer) was changed as shown in Table 5. Note that a polyimide film was used as the substrate. <Example 74> The conductive hot-melt adhesive layer 1 and conductive layer 1 obtained in the preparation of the conductive hot-melt adhesive layer and the preparation of the conductive layer described above were laminated by printing onto a substrate, conductive layer 1, and conductive hot-melt adhesive layer 1 in that order, and further the insulating hot-melt adhesive layer 1 obtained in the preparation of the insulating hot-melt adhesive layer 1 described above was formed on the substrate by printing to obtain Example 74 (conductive laminate sheet 74). Examples 75 to 77 were prepared in the same manner as in Example 74, except that the configuration within the conductive laminate (combination of the conductive hot melt adhesive layer, the conductive layer, and the insulating hot melt adhesive) was changed as shown in Table 5. Note that a polyimide film was used as the substrate.
[0057] The abbreviations for the thermoplastic resins, tackifiers, softeners, and other components in Tables 1 to 4 are shown below.
[0058] <Thermoplastic resin> ·SEBS1: Clayton Corporation Product name: G1652 ·SEBS2: Clayton Corporation Product name: G1726 SEBS3: Clayton Corporation Product name: G1650 ·SEBS4: Clayton Corporation Product name: G1651 SBS1: Clayton Corporation Product name: D0243 SBS2: Clayton Corporation Product name: D4433 SIS1: Clayton Corporation Product name: D1117 SIS2: Clayton Corporation Product name: D1114 SEPS1: Kuraray Co., Ltd. Product name: SEPTON 2063 SEPS2: Kuraray Co., Ltd. Product name: SEPTON 2005 SEPS3: Kuraray Co., Ltd. Product name: SEPTON HG-252 Phenoxy 1: Mitsubishi Chemical Corporation Product name: JER1256 Olefin 1: Ube Maruzen Polyethylene Co., Ltd. Product name: UBEBOND F1100 Olefin 2: Toyobo Co., Ltd. Product name: PMAH3000P Polyamide 1: Henkel Corporation Product name: PA6858 Polyamide 2: Arkema Corporation Product name: Platamide M2519 Polyester 1: Toyobo Co., Ltd. Product name: Byron 200 PVC1: Mitsubishi Chemical Corporation Product name: Sunprene FG40EA (polyvinyl chloride type) EVA1: Mitsui DuPont Polychemicals Co., Ltd. Product name: Evaflex V5733 (ethylene vinyl acetate type) EPDM1: JSR Corporation Product name: EP96 (Ethylene-propylene-diene rubber)
[0059] <Tackifier> Tackifier 1: Arakawa Chemical Co., Ltd. Product name: P-100 Tackifier 2: Harima Chemical Co., Ltd. Product name: Haritack F Tackifier 3: Yasuhara Chemical Co., Ltd. Product name: YS Polyster T30 Tackifier 4: Arakawa Chemical Co., Ltd. Product name: P-90
[0060] <Softener> Softener 1: Idemitsu Kosan Co., Ltd. Product name: Diana Process Oil NS90S Softener 2: Idemitsu Kosan Co., Ltd. Product name: Diana Process Oil PW90 Softener 3: Nippon Sun Oil Co., Ltd. Product name: SUNPUREN100 Softener 4: Fujifilm Wako Pure Chemical Corporation Product name: Dicyclohexyl phthalate
[0061] <Other ingredients> Liquid rubber 1: Kuraray Co., Ltd. Product name: Kuraray LIR290 Antioxidant 1: BASF Product name: Irganox 1010 Copper foil: AS ONE Corporation (size 100 x 300 x 0.03 mm)
[0062] The abbreviations for the conductive fillers listed in Table 1 are as follows. Filler 1: SEC Carbon Co., Ltd. Product name: SGO-10 (graphite) Filler 2: CABOT Corporation Product name: VULCAN XC-72R (carbon black) Filler 3: Lion Specialty Chemical Co., Ltd. Product name: EC300J (carbon black) Filler 4: Lion Specialty Chemical Co., Ltd. Product name: EC200L (carbon black) Filler 5: Lion Specialty Chemical Co., Ltd. Product name: EC600JD (carbon black) Filler 6: Nippon Graphite Industry Co., Ltd. Product name: CMX-100 (graphite) Filler 7: Nippon Graphite Industry Co., Ltd. Product name: LEP (graphite) Filler 8: OCSiAl Company Product name: TUBALL SWCNT (CNT) Filler 9: i-Tech Co., Ltd. Product name: iGurafen-α (graphene) Filler 10: Fukuda Metal Foil and Powder Co., Ltd. Product name: Ag-XF301S Filler 11: Taimei Chemical Industry Co., Ltd. Product name: Taimicron TM-DA
[0063] The resulting layer was then used to carry out the following tests.
[0064] 1. Measurement of volume resistivity (conductive hot melt adhesive layers 1-69) The laminate of the layer and the substrate obtained in the conductive hot melt adhesive layers 1 to 69 was cut into a size of 1.5 cm x 3 cm, and the volume resistivity of the conductive hot melt adhesive layer was measured using a low resistivity meter (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GX MCP-T700). Evaluation was performed on a three-level scale. If the evaluation was "1" or "2," this claim was met. 1: Volume resistivity is 1×10 -1 Ωcm or more 1×10 0 Less than Ωcm 2: Volume resistivity is 1×10 0 Ωcm or more 1×10 3 Less than Ωcm 3: Volume resistivity is 1×10 3 Ωcm or more
[0065] 2. Measurement of volume resistivity (conductive layers 1 to 8) The laminates of the conductive layers and the substrate obtained in the conductive layers 1 to 8 were cut to 1.5 cm x 3 cm, and the volume resistivity of the conductive layers was measured using a low resistivity meter (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GX MCP-T700). Evaluation was performed on a three-level scale. When the evaluation was "1", the present claim was met. Commercially available copper foil was used for the conductive layer 8. 1: Resistivity is 1×10 -5 Ωcm or more 1×10 0 Less than Ωcm 2: Resistivity is 1×10 0 Ωcm or more 3: Resistivity is 1×10 -5 Less than Ωcm
[0066] 3. Measurement of elastic modulus (conductive hot melt adhesive layers 1-69, insulating hot melt adhesive layers 1-3) The conductive hot melt adhesive layer and the insulating hot melt adhesive layer were subjected to tensile tests using a Shimadzu Corporation EX-SX tensile tester. The sheets obtained from the conductive hot melt adhesive layers 1-69 and the insulating hot melt adhesive layers 1-3 were cut into 5mm x 1mm x 24mm pieces to be used as measurement samples. After placing the measurement samples at 25°C, the crosshead speed was set to 50mm / min., and the crosshead displacement and the load history immediately before breakage were measured. The longitudinal strain of the measurement samples was also measured using a strain gauge. The elastic modulus was calculated from the obtained stress-strain curve. ◎: Elastic modulus less than 1MPa ○: Elastic modulus is 1 MPa or more and less than 5 MPa ×: Elastic modulus is 5 MPa or more
[0067] 4. Measurement of Resistance Value (Examples 1 to 77, Comparative Examples 1 to 6) The conductive laminates of the conductive layer (thickness 5 to 30 μm) and the conductive hot melt adhesive layer (thickness 50 to 200 μm) obtained in Examples 1 to 77 and Comparative Examples 1 to 6 were peeled off from the substrate, if any, to obtain a two-layer free film, which was then cut into 4 cm squares. Probes were placed on the conductive hot melt adhesive layer and the conductive layer on the back side, and the resistance value in the conductive laminate was measured by the four-terminal method using a digital multimeter (Keysight Technologies, Inc.: 34410A). I did. The evaluation was carried out on a three-level scale as follows: ◎: Resistance is 1Ω or more and less than 100Ω ○: Resistance is 100Ω or more but less than 1000Ω ×: Resistance is 1000Ω or more
[0068] 5. Measurement of Adhesive Strength (Examples 1 to 77, Comparative Examples 1 to 6) The adhesive strength of the conductive laminate was measured using a tensile tester EX-SX manufactured by Shimadzu Corporation. The measurement samples were prepared by attaching the conductive hot melt adhesive layer of the conductive laminate obtained in Examples 1 to 77 and Comparative Examples 1 to 6, which is composed of a conductive hot melt adhesive layer (50 to 200 μm thick), a conductive layer (5 to 30 μm), and a substrate in that order, to various adherends of 7 cm x 7 cm (surface treatment was performed in advance with a grinder in the case of concrete), and pressing a press plate of 3 cm x 7 cm from above for 1 minute while applying a pressure of 0.1 MPa at a temperature of 200°C. After heating, the sample was left for 24 hours until it returned to room temperature, and used as the measurement sample. The measurement method was to adjust the measurement sample in which the conductive laminate was attached to the adherend to a width of 25 mm, and calculate the adhesive strength from the load when the edge of the sheet was peeled off at an angle of 90 degrees at a speed of 50 mm / min., and evaluate it in three stages according to the following. ◎: Adhesive strength is 10N or more ○: Adhesive strength is 2N or more and less than 10N ×: Adhesive strength is less than 2N Grinder used: Monotaro Slim Disc Grinder (MRO-100DG) Heat press machine used: TP-701B
[0069] 6. Evaluation of durability (Examples 1 to 77, Comparative Examples 1 to 6) The durability of the conductive laminate was judged by creating a conductive laminate in which a conductive layer 1 cm wide and 10 cm long was layered with a conductive hot melt adhesive layer 1 cm wide and 6 cm long, and placing this in a complex cycle test environment to accelerate deterioration. The change in resistance after one week was calculated and the product was rated on a three-point scale as follows: ◎: Resistance change rate is less than 1% ○: Resistance change rate is 1% or more but less than 10% ×: Resistance is 10% or more The combined cycle test method was based on the automobile standard JASO M609, which is a group standard of the Society of Automotive Engineers of Japan.
[0070] 7. Preparation and Evaluation of Natural Potential Sensors (Examples 1 to 77, Comparative Examples 1 to 6) The measurement sample was prepared by attaching the conductive hot melt adhesive layer (thickness 200 μm) of the conductive laminate obtained in Examples 1 to 77 and Comparative Examples 1 to 6 to the concrete surface of reinforced concrete where rusting of the reinforcing bars had progressed, and adhering it to the concrete surface by pressing it with a flat plate for 1 minute while applying a pressure of 0.1 MPa while heating it to 200 ° C from above. After heating, the sample was left for 24 hours until it returned to room temperature, and used as the measurement sample. The natural potential was measured by connecting a voltmeter between the conductive laminate and the wiring connected to the reinforcing bars in the concrete. The natural potential sensor, which can judge the progress of reinforcing bar corrosion, was evaluated by marking the measured potential value as ○ if it was -100 mV or less and × if it was -100 mV or more. A digital multimeter 34465A manufactured by Keysight Technologies was used for the natural potential measurement.
[0071] 8. Preparation and Evaluation of Chloride Ion Sensors (Examples 1 to 77, Comparative Examples 1 to 6) To make the chloride ion sensor, the chloride amount was 1 m 3 Two types of concrete structures were produced, with 1.0 kg and 10 kg per unit weight. Measurement samples were produced by attaching the surfaces of the two conductive laminates obtained in Examples 1 to 77 and Comparative Examples 1 to 6, with the conductive hot melt adhesive layer (thickness 200 μm) on the concrete surface in a pair separated by a distance of 10 cm, and then heating them to 200°C and pressing them with a flat plate for 1 minute while applying a pressure of 0.1 MPa to bond them to the concrete surface. After heating, the samples were left to stand for 24 hours until they returned to room temperature, which was used as the measurement sample. An LCR meter (impedance measuring device) was connected between the wiring connected to one conductive laminate and the other conductive laminate, making it possible to measure the AC impedance. The chloride amount of 1 m 3 Compared with the AC impedance value when a concrete structure containing 1.0 kg of chloride per m 3The chloride ion sensor that measures chloride ion concentration was evaluated by marking it with an O if the AC impedance value was small when using a concrete structure containing 10.0 kg per unit area, and with an X if it was otherwise.
[0072] [Table 1]
[0073] [Table 2]
[0074] [Table 2]
[0075] [Table 3]
[0076] [Table 4]
[0077] [Table 5]
[0078] [Table 5] [Explanation of symbols]
[0079] 1 Base material 2 Conductive layer 3 Conductive hot melt adhesive layer 4 Adherent 5. Sealing layer 6 Insulating hot melt adhesive layer 7 Wiring 8. Steel Bars 9. Concrete 10 Potentiometric detector 11 Impedance Measuring Instrument 20 Conductive laminate 30 Adhesive structure
Claims
1. A conductive laminate having at least a conductive layer and a conductive hot melt adhesive layer in contact with the conductive layer on a substrate, the conductive hot melt adhesive layer having a volume resistivity of 1×10 -1 Ωcm or more 1×10 3 The volume resistivity of the conductive layer is less than 1×10 -5 Ωcm or more 1×10 0 the conductive layer and the conductive hot melt adhesive layer each contain a resin and a conductive filler; A conductive laminate, characterized in that the conductive filler is a carbon-based filler or a metal filler, the content ratio of the carbon-based filler to the entire conductive layer is 10 to 80% by weight, and the content ratio of the metal filler to the entire conductive layer is 40 to 80% by weight.
2. 2. The conductive laminate according to claim 1, wherein the conductive hot melt adhesive layer has an elastic modulus of less than 5.0 MPa at 25°C.
3. 3. The conductive laminate according to claim 1, wherein the conductive layer and / or the conductive hot-melt adhesive layer is patterned.
4. 4. The conductive laminate according to claim 3, further comprising a patterned insulating hot-melt adhesive layer around the periphery of the patterned conductive layer and / or the patterned conductive hot-melt adhesive layer.
5. The conductive laminate according to any one of claims 1 to 4, characterized in that the conductive filler contains at least one selected from the group consisting of graphite, carbon black, carbon nanotubes, graphene, graphene oxide, silver, copper, tin, zinc, zinc oxide, nickel, manganese, and ITO.
6. 6. The conductive laminate according to claim 5, wherein the conductive filler comprises at least one selected from the group consisting of graphite, carbon black, carbon nanotubes, graphene, and graphene oxide.
7. The conductive laminate according to any one of claims 1 to 6, characterized in that the resin in the conductive hot melt adhesive layer contains a styrene-based thermoplastic resin, and the resin in the conductive layer contains a phenoxy-based thermoplastic resin.
8. 8. The conductive laminate according to claim 1, wherein the conductive hot-melt adhesive layer and / or the insulating hot-melt adhesive layer has adhesiveness.
9. 9. A bonded structure comprising the conductive laminate according to claim 1 and an adherend laminated thereon.
10. A natural potential sensor capable of measuring the deterioration of reinforcing bars present inside concrete through a signal obtained from a conductive laminate, the natural potential measurement sensor being characterized in that the conductive laminate is a conductive laminate as defined in any one of claims 1 to 8.
11. A chloride ion sensor capable of measuring the chloride ion concentration inside concrete through a signal obtained from a conductive laminate, comprising: A chloride ion sensor comprising the conductive laminate according to any one of claims 1 to 8.
12. A method for producing a conductive laminate having at least a conductive layer and a conductive hot melt adhesive layer adjacent to the conductive layer on a substrate, the method comprising the steps of: printing the conductive layer on the substrate; and printing the conductive hot melt adhesive layer, the conductive hot melt adhesive layer having a volume resistivity of 1×10 -1 Ωcm or more 1×10 3 The volume resistivity of the conductive layer is less than 1×10 -5 Ωcm or more 1×10 0 a conductive layer and a conductive hot-melt adhesive layer each containing a resin and a conductive filler, the conductive filler being a carbon-based filler or a metal filler, the content ratio of the carbon-based filler in the entire conductive layer being 10 to 80% by weight, and the content ratio of the metal filler in the entire conductive layer being 40 to 80% by weight.
Citation Information
Patent Citations
Method for measuring potential of reinforcing bar in concrete
JP1986124863A
Conductive adhesion sheet and wiring material using it
JP1996106818A
Concrete structure capable of detecting defect in coated reinforcing bar and its detecting method
JP1999230927A
Electroconductive resin composition for adhesion
JP2001200225A
Conductive hot melt silicone adhesive composition
JP2002155261A